PROPORSI DEWAN KOMISARIS INDEPENDEN SEBAGAI PEMODERASI PENGARUH KEPEMILIKAN INSTITUSIONAL PADA MANAJEMEN LABA - Dananjaya, Dewa Gede Yudha; Agus Ardiana, Putu (E-Jurnal Akuntansi; Vol 15 No 2 (2016), 2016)
This study aims to prove the influence of institutional ownership in earnings management to the proportion of independent board as moderating variables. The research sample is manufacturing companies listed in Indonesia Stock Exchange in 2012-2014 as many as 61 companies of observation after the purposive sampling. The data analysis technique used is the interaction is often called the moderated regression analysis. The results provide evidence that companies that have institutional ownership significant positive effect on earnings management and the proportion of independent board can be moderate (weaken) the influence of institutional ownership on earnings management so that companies that have institutional ownership will improve management practices earnings but in the presence of independent directors practice earnings management can be minimized.
Keywords: Earnings Management, Institutional Ownership, proportion of Independent Commissioner Board